KERANGKA KONSEP ASSESSMENT OF LEARNING, ASSESSMENT FOR LEARNING, DAN ASSESSMENT AS LEARNING SERTA PENERAPANNYA PADA PEMBELAJARAN - Giati Anisah (Pendidikan Agama Islam, 2021)
This paper aims to explain the assessment of learning, assessment for learning, and assessment as learning-based internet learning, using library research and descriptive analysis method. Data obtained from various library sources, both books and journals, both printed and online, relate to the concepts of assessment of learning, assessment for learning, and assessment as learning. Based on the results of the analysis it was found that each approach has its contribution to student learning. This is because the objectives of each approach are different. Assessment of learning aims to consider student placement, grade promotion, and awarding certificates. While the assessment for learning aims to provide information to teachers about the achievement of student competencies so that teachers can make decisions about the next learning. On the other hand, assessment as learning aims to monitor and self-correct students independently by students. Judging from the benchmarks that are used as comparisons, in the assessment of learning the comparisons are other students. In the assessment for learning, there are criteria made by the teacher or expectations. Meanwhile, in assessment as learning, the benchmark used is the student's personal goals. The key assessors in the assessment of learning and assessment for learning are teachers, while in assessment as learning the key assessors are students.